Full Process Modeling and Correction Strategies for Electricity Spot Market Considering AC Feasibility Check - Hongbo WANG; Lizheng SHAO; Qing XIA; Xinxin FANG; Xiaoting CHEN; Hengyi LIU (Zhongguo dianli)
The market clearing results of spot market need to be delivered to the generators after passing N-1 security contingency analysis and AC feasibility check. In existing methods, the check procedures are split from pricing model, which leads to the deviation between the market results and the practical operation instructions and incurs uplift payment. To resolve this problem, a study is made on the full-process modeling and correction strategies in spot market. Firstly, a dispatching model with consideration of the power peak shaving requirement is formulated, and it is proved based on the KKT condition that the LMPs can guarantee storage devices’ and traditional generators’ incentive compatibility. Then, an AC power flow based feasibility restoration model is established, which incorporates the restoration cost into the dispatching and pricing model. Finally, under the circumstances of violations, the strategies for market correction and out-of-market correction are proposed to meet different requirements of market clearing time. It is verified with case study that the proposed method can effectively restore the AC feasibility. When there is no time restriction, the market correction method has advantages over other methods. When there is a time restriction, the convex relaxation based out-of market correction method obtains less operation cost and market surplus than the PTDF-based correction method.